2014
DOI: 10.3732/ajb.1300449
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny, character evolution, and biogeography of Cuscuta (dodders; Convolvulaceae) inferred from coding plastid and nuclear sequences

Abstract: Hybridization may play an important yet underestimated role in the evolution of Cuscuta. Our results disagree with scenarios of evolution (polarity) previously proposed for several taxonomically important morphological characters, and with their usage and significance. While several cases of long-distance dispersal are inferred, vicariance or dispersal to adjacent areas emerges as the dominant biogeographical pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
114
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(125 citation statements)
references
References 61 publications
(95 reference statements)
9
114
0
2
Order By: Relevance
“…Thus, to reconstruct ancestral character states in Cuscuta we analyzed the distribution of character states in-group (Welsh et al, 2010;Wright et al, 2011;Riviere et al, 2013). Adding putative outgroup Convolvulaceae and coding them with a different character state than the in-group Cuscuta (García et al, 2014) produced similar results (results not shown). Scenarios of character evolution were analyzed using the parsimony reconstruction method implemented in Mesquite 2.75 (Maddison and Maddison, 2011).…”
Section: Character Evolutionmentioning
confidence: 57%
See 4 more Smart Citations
“…Thus, to reconstruct ancestral character states in Cuscuta we analyzed the distribution of character states in-group (Welsh et al, 2010;Wright et al, 2011;Riviere et al, 2013). Adding putative outgroup Convolvulaceae and coding them with a different character state than the in-group Cuscuta (García et al, 2014) produced similar results (results not shown). Scenarios of character evolution were analyzed using the parsimony reconstruction method implemented in Mesquite 2.75 (Maddison and Maddison, 2011).…”
Section: Character Evolutionmentioning
confidence: 57%
“…This is significant because until now stem morphology was not considered relevant for the systematics of the genus (e.g., Yuncker, 1932). Also, these stem types are important because the only available morphological characters at subgeneric levels have been a few gynoecium characters (Wright et al, 2011;García et al, 2014;Costea et al, 2015).…”
Section: Systematic Significance Of Multicellular Protuberancesmentioning
confidence: 99%
See 3 more Smart Citations